Surgical Outcomes Of Rhegmatogenous Retinal Detachment In Young Adults Ages 18–30 Years - Brown K (Dove Medical Press, 2019)
Karen Brown, Nicolas A Yannuzzi, Natalia F Callaway, Nimesh A Patel, Nidhi Relhan, Thomas A Albini, Audina M Berrocal, Janet L Davis, Jorge A Fortun, William E Smiddy, Jayanth Sridhar, Harry W Flynn Jr, Justin H Townsend Department of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Justin H TownsendDepartment of Ophthalmology, Bascom Palmer Eye Institute, University of Miami Miller School of Medicine, 900 NW 17th Street, Miami, FL 33136, USATel +1305 326-6000Fax +1305 326-6417Email jtownsend@med.miami.eduPurpose: The purpose of this study is to investigate associations with and surgical outcomes of rhegmatogenous retinal detachment (RRD) in young adults.Methods: This is a retrospective consecutive case series of patients aged 18–30 years who underwent surgical repair for RRD between January 1, 2014 and December 1, 2016 at a university referral center.Results: The current study includes 38 eyes with RRD. Documented high or moderate myopia was present in 28 (74%) eyes. Connective tissue disease was present in 3 (8%) eyes. Median pre-operative visual acuity (VA) was 20/70. Surgery was performed via scleral buckle (SB) alone in 27/38 (71%) and via combined SB and pars plana vitrectomy (SB/PPV) in 11/38 (29%) eyes. Single surgery anatomical success (SSAS) rate was 20/27 (74%) for SB and 7/11 (64%) for SB/PPV. The retina was reattached at last follow-up in 25/27 (93%) for SB and 11/11 (100%) for SB/PPV. The median postoperative VA was 20/40.Conclusion: In the current study of young adults with RRD, the most common association was high or moderate myopia. Visual and anatomic outcomes at last follow-up were generally favorable.Keywords: myopia, rhegmatogenous retinal detachment, RRD, young adults